Evolution mechanism for a surface gradient nanostructure in GH4169 superalloy induced by an ultrasonic surface rolling process - Yang, Jing; Liu, Daoxin; Li, Mengyao; Ren, Zhencheng; Liu, Dan; Xu, Xingchen; Zhang, Xiaohua; Zhang, Hao; Xiang, Junfeng; Ye, Chang (Materials science & engineering. A, Structural materials : properties, microstructure and processing, 2023)
In this study, the evolution mechanism of surface gradient nanostructure induced by the ultrasonic surface rolling process (USRP) in GH4169 superalloy was investigated. The gradient nanostructure, which was characterized using transmission electron microscopy, revealed that the repeated impacts induced by USRP produced a gradient nanostructure with a thickness of ∼330 μm at the surface of the material. Equiaxed nanograins with an average grain size of ∼30 nm were observed on the topmost surface, and the grain size gradually increased with depth. In the nanocrystallization mechanism, dislocations first formed as a result of the initial plastic strain introduced by USRP. Next, dislocation tangles and dislocation walls were formed and gave rise to the formation of low-angle and high-angle grain boundaries, which resulted in grain refinement. As plastic strain accumulated, nanoscale deformation twins were formed. The interaction between dislocations and deformation twins further refined the parent grains to produce equiaxed nanograins with high-angle grain boundaries. In addition, stacking faults were generated when the interaction between dislocations and deformation twins was initiated. A 9R structure was observed inside the nanograins at the topmost surface that significantly improved the work-hardening capacity of the superalloy by acting both as dislocation blockers and dislocation storage sites. The microhardness of the nanostructured GH4169 superalloy was improved by 67% as compared to the untreated material.